2020
DOI: 10.1137/19m1242513
|View full text |Cite
|
Sign up to set email alerts
|

Circular Flows in Planar Graphs

Abstract: For integers a ≥ 2b > 0, a circular a/b-flow is a flow that takes values from {±b, ±(b+1), . . . , ±(a−b)}. The Planar Circular Flow Conjecture states that every 2k-edge-connected planar graph admits a circular (2 + 2 k )-flow. The cases k = 1 and k = 2 are equivalent to the Four Color Theorem and Grötzsch's 3-Color Theorem. For k ≥ 3, the conjecture remains open. Here we make progress when k = 4 and k = 6. We prove that (i) every 10-edge-connected planar graph admits a circular 5/2-flow and (ii) every 16-edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The case k = 1 is simply Grötzsch's theorem [3]; for k = 2, it has been verified by Dvořák and Postle [2] for the girth condition 10; for k = 3, the best-known girth bound of 16 has very recently been achieved by Postle and Smith-Roberge [20]. The same results for k = 2, 3 were independently obtained by Cranston and Li [1] using the notion of flows. The results of [2] and [20] are each proved by establishing lower bounds on the density of C k 2 +1 -critical graphs, as follows.…”
Section: Further Contextmentioning
confidence: 66%
“…The case k = 1 is simply Grötzsch's theorem [3]; for k = 2, it has been verified by Dvořák and Postle [2] for the girth condition 10; for k = 3, the best-known girth bound of 16 has very recently been achieved by Postle and Smith-Roberge [20]. The same results for k = 2, 3 were independently obtained by Cranston and Li [1] using the notion of flows. The results of [2] and [20] are each proved by establishing lower bounds on the density of C k 2 +1 -critical graphs, as follows.…”
Section: Further Contextmentioning
confidence: 66%
“…-coloring follows from [25]. Alternative proofs of these two results (for k = 2, 3) are given in [4]. For general values of k, the best results follow from the general results on flows mentioned above.…”
mentioning
confidence: 91%
“…Similarly, that every planar graph of odd‐girth at least 17 admits a circular 73 $\frac{7}{3}$‐coloring follows from [25]. Alternative proofs of these two results (for k=2,3 $k=2,3$) are given in [4]. For general values of k $k$, the best results follow from the general results on flows mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…For partial results of Conjecture 1.1, Dvořák and Postle [13] showed that every planar graph of girth at least 10 is C 5 -colorable. In [11], by duality from flow results, a simpler proof of Dvořák and Postle's result was obtained, and it was extended to the next case that every planar graph of girth at least 16 is C 7colorable. Independently, Postle and Smith-Roberge [23] also proved that every planar graph of girth at least 16 is C 7 -colorable through the density of C 7 -critical graphs.…”
Section: Introductionmentioning
confidence: 99%